Corps transitoires, images errantes. Steven Cohen, the Wandering queer - Yann-Guewen Basset (Images Re-Vues)
In a retrospective approach of the whole work of the visual and performance artist Steven Cohen (1962‑ …), this paper questions different forms of transition which appears in it and contribute to transform the artist into an original “wandering queer”. Firstly, based on a focus on the performance and installation The Wandering Jew (2010) through its traces, the author consider how the mythical figure of the wandering jew influence Cohen’s aesthetic and affect his relation to space, movement, gender and history, going far beyond a simple reference to Jewish culture. From public activism to perfoming arts, from visual or cinematographic to real presence, interweaving traumatic memories (Apartheid, Shoah), Steven Cohen defines a specific queer aesthetic, based on dispersion and ectasis rather than only gender subversion or parody.